ANALYSIS OF STRATEGIC PLANNING AND MARKETING STRATEGY TOWARDS THE DEVELOPMENT OF ECO GREEN CITY IN PT. ADVANCED INDONESIAN ENERGY - Sigit Wisnu Dermawan; Yani Soleha; Arini Egi Tiarawati; Edi Hamdi; Tantri Yanuar Rahmat Shah; Ferryal Abadi (Jurnal Ilmiah Jendela Pendidikan, 2021)
Marketing plays an important role in the strategic planning process. Marketing management provides the greatest functional contribution in the strategic planning process to obtain the desired results based on the prevailing conditions and structures by using the best resources and company advantages to achieve its goals. This study aims to analyze the marketing strategy towards the development of an eco green city at PT. Advanced Indonesian Energy. This type of research uses descriptive research with a qualitative approach. Sources of data used are primary data and secondary data. Data collection techniques using interviews and documentation. The information obtained from the data collection was analyzed in three ways, namely reduction, data presentation, conclusion drawing and verification. The results of the study are based on the QSPM strategy from PT Energi Indonesia Maju which will focus on building closeness with the PLTU to conduct waste co-firing, so the main objective of marketing is to ensure coordination and operational approval of the PLTU Indramayu and the local government of Tasikmalaya in the short term. Prior to full operation, the main objective of marketing is to ensure long-term cooperation with PLTU Indramayu. With a long-term cooperation with PLTU, the company can also ensure its sustainability.